Multidecadal Historical Trends in Tropical Cyclone Intensity and Evolution Characteristics for Two North Atlantic Subbasins. Issue 17 (9th September 2019) - Ge, Kelsey; Colle, Brian A.
Abstract: This paper investigates the relationship between long‐term trends (1980–2017) in intensity and wind evolution for tropical cyclones (TCs) within the western tropical Atlantic (WTA) and central/eastern tropical Atlantic (CETA) subbasins. Long‐term TC trends in intensity, intensification time, and wind variability for the CETA were generally more significant than, and in some cases opposite to, those for the WTA. Both the TC intensity levels, as measured by the power dissipation index normalized by storm hours and proportion of rapid intensification intervals (defined as a 12‐hr wind speed increase of 20 kt or more), exhibit no long‐term trends in either subbasin. A TC wind variability index (WVI) calculated over 72‐hr intervals of the TC lifecycle decreases for the WTA over the decades, while the CETA has the 72‐hr intervals with the greatest wind speed fluctuations. The average period of intensification before the peak in TC intensity increases ~0.97 hr/year for the CETA. TC maximum intensity exhibits no trend, suggesting that TCs in the tropical North Atlantic have a trend favoring a longer intensification period to reach their lifetime maximum intensity. A correlation analysis suggests that warmer sea surface temperatures and greater moisture favor longer intensification and greater WVI. In contrast, greater 850‐ to 200‐hPa vertical wind shear is associated with shorter intensification periods and less WVI. Plain Language Summary: Wind speed data from tropical cyclones and hurricanes over the past four decades were used to quantify various cyclone characteristics, such as intensity, intensification, and wind speed fluctuations. Observed trends over time were then compared to environmental conditions that may be driving the changes, such as heat, moisture, and wind composition of the surrounding environment during cyclone genesis. This two‐prong approach not only reveals the manifest ways in which tropical cyclone evolution has changed over time but also points to the long‐term environmental changes that are associated with these trends and how they may be related to climate change. The analyses were conducted by dividing the tropical North Atlantic Ocean into a western and central/eastern portion and evaluating them separately. While the western tropical Atlantic demonstrated little to no long‐term trends, the central and eastern tropical Atlantic exhibited significant increases in cyclone buildup time and short‐term wind speed fluctuations. When compared to the surrounding environmental factors, the intensification time was found to decrease with conditions that favored cyclone formation, while the wind speed variability increased. Key Points: Tropical cyclone (TC) wind variability decreases in the western tropical North Atlantic and is greatest in the central eastern Atlantic The average period of intensification before peaks in TC intensity increases ~0.33 hr/year for both North Atlantic subbasins combined Higher sea surface temperature and moisture and lower vertical wind shear are associated with longer intensification and wind variability